2022
DOI: 10.1002/ijc.34292
|View full text |Cite
|
Sign up to set email alerts
|

Associations between early‐life and in utero infections and cytomegalovirus‐positive acute lymphoblastic leukemia in children

Abstract: Childhood infections and cytomegalovirus (CMV) are associated with pediatric acute lymphoblastic leukemia (ALL). CMV dysregulates the host immune system and alters the immune response to subsequent antigenic exposures. We suspect that this immune dysregulation contributes to increased numbers of symptomatic infections in childhood allowing for expansion of pre‐leukemic clones. We explored the association between childhood infections, maternal infections during pregnancy and CMV‐positive ALL. Using a droplet di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…1 In the same year, Kinlen proposed that childhood leukemia was caused by an abnormal immune response in a susceptible population due to migration and population mixing related to a lack of herd immunity. 2 Currently, many studies have suggested a positive association between postnatal infection and acute lymphoblastic leukemia (ALL), [3][4][5] as some literature has proposed protective effects or no evidence for any connection between infection and ALL. 6,7 On the other hand, there is little detailed research on specific types of infections 8,9 and on subtypes of leukemia such as acute myeloid leukemia (AML).…”
Section: Introductionmentioning
confidence: 99%
“…1 In the same year, Kinlen proposed that childhood leukemia was caused by an abnormal immune response in a susceptible population due to migration and population mixing related to a lack of herd immunity. 2 Currently, many studies have suggested a positive association between postnatal infection and acute lymphoblastic leukemia (ALL), [3][4][5] as some literature has proposed protective effects or no evidence for any connection between infection and ALL. 6,7 On the other hand, there is little detailed research on specific types of infections 8,9 and on subtypes of leukemia such as acute myeloid leukemia (AML).…”
Section: Introductionmentioning
confidence: 99%